Toward Sustainable Islamic Fintech: Legal Challenges and Strengthening Sharia Governance in Indonesia - Lahfiz Safutra; Aziz Asyraf (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The development of financial technology (fintech) has brought significant transformations to the financial services system, including in the Islamic finance sector in Indonesia. Sharia fintech has emerged as an alternative to digital financial services, with the expectation that it will remain grounded in the principles of Islamic economic law. However, technology-based product innovations also raise various legal issues related to Sharia compliance. This study aims to analyze the concept of sharia compliance, the legal regulation of sharia fintech in Indonesia, and its implementation in sharia fintech product innovation. The research employed normative legal methods, drawing on legislative, conceptual, and fatwa approaches. Data was obtained through a literature study of legislation, DSN-MUI fatwas, and Islamic economic law literature. The study's results indicate that the legal regulation of sharia fintech in Indonesia is normatively adequate, supported by the roles of the OJK, Bank Indonesia, and DSN-MUI. However, in practice, the implementation of Sharia compliance in fintech product innovation still faces various challenges, such as the risk of hidden usury, ambiguous contracts, the use of late fees, and weak substantive supervision. Therefore, it is necessary to strengthen adaptive regulations, enhance the competence of the Sharia Supervisory Board, and strengthen public Sharia financial literacy so that Sharia fintech can develop sustainably and in accordance with the principles of Sharia economic law.